PENGEMBANGAN PEMBELAJARAN ETNOMATIKA: INTEGRASI BUDAYA DAN MATEMATIKA - Siregar, Isma Novia (DIRASATUL IBTIDAIYAH, 2023)
This research aims to explore and analyze the integration of ethnomathematics in mathematics education within the context of students' living environments. Utilizing a literature review method, this study systematically examines relevant literature on ethnomathematics and mathematics education to gain profound insights. The research focuses on identifying ethnomathematics concepts and their application in the context of mathematics education, particularly within the communities where students reside. Through the evaluation of case studies and previous research, the study aims to draw conclusions regarding the effectiveness of integrating ethnomathematics in enhancing students' understanding of mathematical concepts. The findings are expected to guide education practitioners in designing more relevant and meaningful teaching strategies, promoting a strong connection between formal mathematical concepts and the cultural contexts and life experiences of students. The research is anticipated to make a positive contribution to the development of more contextual and student-centered mathematics education. Keywords: Ethnomathematics; Innovative Learning; Cultural Integration; Mathematical Concepts;Local Wisdom.